Assessing the return on investment of injury prevention procedures in professional football - Fuller, C. W. (Sports Medicine, 2019)
The aim of this study was to develop a quick and simple screening procedure for evaluating the return on investment provided by injury prevention programmes in professional football. Injury prevention in sport has usually been considered in isolation of other management responsibilities, and interventions are published irrespective of whether their impact is worthwhile and irrespective of the return on players` time investment in the programme. This approach is naive from a business perspective and is not an approach normally adopted by commercial organisations. Methods: In professional football, the overwhelming cost associated with implementing an injury prevention programme is the players` time commitment, and the major benefit is the players` increased availability, achieved through the reduction in the number of injuries. A comparison of these time-based costs and benefits provides the basis for the evaluation process presented. Results: Applying the evaluation process to a number of published injury prevention programmes recommended for football demonstrates that they are unlikely to provide an adequate return on investment. Conclusions: Researchers should focus on developing injury prevention programmes that provide an adequate return on players` time investment, otherwise there is no incentive for clubs to implement the programmes. Reporting that an injury prevention programme produces a statistically significant reduction in the incidence of injury, for example, is insufficient information. Injury prevention programmes should focus on `at risk` players to increase the return on investment, and researchers should evaluate and report on the utility of prevention programmes within the intended sports setting.